IMPROVING THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT BY USING CHAIN WRITING - Novri Susanti Suparman (STAI Nurul Falah Airmolek, 2019)
Writing is most likely to encourage thinking and learning when the students view writing as a process. By recognizing that writing is a recursive process and every writer uses process in a different way, students experience less pressure to “get it right the first time” and more willing to experiment, explore, revise, and edit. Yet, novice writers need to practice “writing” or exercises that involved copying or reproduction of learned material in order to learn the conventions of spelling, punctuation, grammatical agreement, and the like. Furthermore, students need to write in the language through engaging in variety of grammar practice activities of controlled nature